Studies of Thorium(IV) and Dioxouranium(VI) Complexes of a Schiff Base: Part 2. - KHAN , A.R.; ARORA, KISHOR; SHARMA, K.P. (Asian Journal of Chemistry, 2010)
A new series of Th(IV) and UO2 (VI) with a Schiff base derived from condensation of p-amino ethylbenzoate and p-(N,N'-dicyanoethyl) amino benzaldehyde having general composition ThX4·nL (X = NO3-, n = 2; X = NCS-, n = 2; X = I-, n = 4; X = ClO4-, n = 6) and UO2X2·2L (X = NO3-), I-, NCS- or CH3COO- ) and UO2(ClO4)2·4L where L is the Schiff base. The complexes were characterized on the basis of analytical conductance, molecular weight and spectral studies. The Schiff base behaves as a neutral monodentate ligand which coordinate to the central metal atom thtough azomethine nitrogen.